(untitled) (Journal of Orofacial Research, 2025)
Odontogenic keratocyst (OKC) is significant in oral and maxillofacial surgery due to its diverse manifestations and high recurrence rate. The treatment protocol for OKC is controversial and treatment modalities range from enucleation to resection including adjunctive procedures like peripheral ostectomy, cryotherapy, and chemical cauterization. This paper discusses eight cases diagnosed with OKC which was confirmed by histopathological examination, and subsequently underwent enucleation along with chemical cauterization with modified Carnoy’s solution. Kinds of literature have proved that enucleation with the application of modified Carnoy’s solution has reduced the recurrence rate considerably. Our case series illuminates that the treatment approach adopted in our institute has decreased the recurrence rate while maintaining functional and esthetic aspects.